Nitrogen removal by different riparian vegetation buffer strips with different stand densities and widths - Jian Lv (IWA Publishing, 2021)
The migration of nitrogen (N) from farmland to lake aggravates eutrophication. Riparian buffer strips (RBSs) are crucial in alleviating nitrogen into water bodies. This study examined the impacts of different RBS patterns on nitrogen removal. The effects of different RBSs of various widths (5, 15, 30, and 40 m), with different vegetation types (Taxodium hybrid ‘Zhongshanshan’, poplar (Nanlin-95), and a mixed forest of T. hybrid ‘Zhongshanshan’ and poplar) and at different densities (400, 1,000, and 1,600 plants·hm−2) on the TN, NH4+-N and NO3−-N removal rates in different depths of runoff water were studied. The results showed that the 15 m-wide RBS removed nitrogen the most effectively, with average removal rates of NH4+-N, NO3−-N and TN reaching 67.79%, 65.93% and 65.08%, respectively. Among the RBSs with different vegetation types, the poplar forest RBS removed the most NH4+-N (74.28%) and NO3−-N (61.71%). The mixed-forest RBS removed the most TN (65.57%). The RBS with 1,000 plants·hm−2 was more suitable in terms of the removal of NH4+-N (74.25%), NO3−-N (71.08%) and TN (62.67%). The conclusion can provide the basis of vegetation and width optimization for the design and construction of an RBS for maximum eutrophication nutrient removal. HIGHLIGHTS Construction and stability of different RBS patterns were operated for around three years.; Removal capacity of N pollutants from runoff by different patterns was compared quantitatively.; The 15 m-wide RBS with 1,000 stem·hm−2 poplar plantation removed nitrogen the most effectively.;